2015
DOI: 10.1371/journal.pone.0122739
|View full text |Cite
|
Sign up to set email alerts
|

The Injured Liver Induces Hyperimmunoglobulinemia by Failing to Dispose of Antigens and Endotoxins in the Portal System

Abstract: Hyperimmunoglobulinemia is frequently observed in patients with chronic liver diseases. However, the exact mechanism underlying the high level of antibody formation is not fully understood. In our study, we provide evidence for the functional role of the liver and the stimulation of plasma cell proliferation in hyperimmunoglobulinemia. We collected sera from patients with chronic liver diseases, and the level of serum immunoglobulins in patients was examined; this was also investigated in animal models of live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
(26 reference statements)
1
10
0
1
Order By: Relevance
“…Albeit less well-known, catabolism of immunoglobulins is one relevant hepatic function in systemic homeostasis. Accordingly, hyperglobulinemia is found in patients and models of severe and chronic liver dysfunction (17,22). Importantly we observed that the hepatic accumulation of IgGs was higher in CCl 4 -treated Slu7 +/mice (Fig.…”
Section: Accepted Articlementioning
confidence: 52%
“…Albeit less well-known, catabolism of immunoglobulins is one relevant hepatic function in systemic homeostasis. Accordingly, hyperglobulinemia is found in patients and models of severe and chronic liver dysfunction (17,22). Importantly we observed that the hepatic accumulation of IgGs was higher in CCl 4 -treated Slu7 +/mice (Fig.…”
Section: Accepted Articlementioning
confidence: 52%
“…In our study, we assayed BMP9 levels in plasma rather than serum and optimised the ELISA protocol to mitigate against false positive or negative findings that commonly arise in ELISAs due to plasma matrix interference and heterophilic antibody crosslinking [42]. The latter could be significant since hyperimmunoglobulinaema is prevalent in patients with liver disease and increases with severity [43]. Similar to Nikolic et al we include goat serum to mitigate heterophilic antibody crosslinking [19].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for increased endogenous IgG level has been reported to be associated with increased B‐cell synthesis. The injured liver fails to dispose of gut antigens and endotoxins, and the bypassed antigens and endotoxins lead to B‐cell activation and proliferation, which increases endogenous IgG production . Normal endogenous IgG level is about 1,000 to 1,400 mg/dL, while the level is increased up to 1,700, 2,000, and 6,000 mg/dL in mild, moderate, and severe HI, respectively …”
Section: Discussionmentioning
confidence: 99%